Carbon Accounting: Its Implications on Accounting Practices and Corporate Sustainability Reports - Syam, Muh. Ardiansyah; Djaddang, Syahril; Adam, Adam; Merawati, Endang Etty; Roziq, Mohammad (International Journal of Economics and Financial Issues, 2024)
Carbon Accounting is a new accounting paradigm on ecological-based economic transactions. It is also known as carbon cost management. The issues regarding carbon cost management will have implications for other strategic issues related to management accounting. The concept and application of Carbon Accounting will also have broad implications for the professions and strategic issues of carbon management accounting. This study focuses on the implication of carbon accounting on accounting practices and corporate sustainability reports. The literature reviews and qualitative analyses were conducted to grab the philosophy, practice and implication of implementation of carbon accounting – carbon cost management. Based on the study, carbon accounting implementation implied to accounting practices and corporate sustainability report. In term of calculating carbon emission or greenhouse gasses, there were four methods as set by Inter-governmental Panel for Climate Change (IPCC) and European Renewable Energy. In term of Corporate Sustainability Report, there were three theories considered: Instrumental Theories, Social & Political Theories and Normative Theories. It is difficult to account for emission allowances, and revealed that there is a potential guidance role for auditors during the absence of an international accounting standard. With the emission allowance assets, there is diversity in the accounting treatment of liabilities, and a considerable level of non-disclosure. In practice, this means that the only liability recognition in the financial statements is for shortfalls in allowances.